Teaching word stress patterns of English using a musically-simulated technique - Mohammad Ali Heidari-Shahreza; Ahmad Moinzadeh (Penerbit UKM, 2012)
The correct placement of word-level stress is a main concern in EFL speech intelligibility training. It is particularly important for EFL learners who have a drastically different stress system in their L1 (e.g. Persian). These learners usually misplace the primary stress in their L2 which subsequently may interrupt the flow of communication and leads to unintelligibility. Therefore, the present study explored the effect of musically-simulated patterns, as a new teaching technique, on the learning of word stress patterns of English. Musically-simulated patterns were defined in the context of the study as impressionistic patterns which were acoustically similar to word stress patterns of English. 30 Iranian EFL elementary learners at a language institute participated in the study. The new technique was used to teach four stress patterns of two- and three-syllable English words. The results of the posttest indicated that the participants in the experimental group (who listened to musically-simulated patterns) obtained significantly higher scores. Moreover, two-syllable words appeared to be more positively influenced by these musical patterns. It is suggested that L1 negative transfer and the inherent cognitive complexity of the stress patterns may contribute to the varying effect of these musical patterns. Finally, the possible applications of using this technique at both levels of material development and classroom practice are discussed.